The effect of severity of club foot based on pirani severity score on the clinical outcome and the foot bimalleolar angle at the end of treatment - Shieng, Chong Teck (2021)
Introduction Persistent foot adduction is one of the residual deformity encountered after clubfoot treatment. Foot bimalleolar angle (FBA) has been recently described for initial clubfoot assessment as an objective, specific and numerical way of assessing foot adduction. There are several clinical and functional outcome scoring system after clubfoot treatment, but clinical outcome assessment by Jain et al is more practical and objective. The aim of this study is to evaluate the correlation of initial Pirani score with FBA and Jain clinical outcome in post treatment patients. Methodology Foot tracings with the level of both the malleoli of children who completed Ponseti treatment for clubfoot from January 2009 to June 2019 were taken. The anteromedial angle between the long axis of foot and the bimalleolar plane was taken as the FBA angle. Initial Pirani severity score was collected from patients’ medical records, and patients were graded post Ponseti treatment according to Jain clinical outcome. Results Comparisons of initial Pirani score, FBA and Jain clinical outcome was done in 26 feet (16 patients). There was a moderate, significantly negative correlation(r = -0.62, p = 0.001, n= 26) between Pirani score and FBA. A child with a unit increase of Pirani score has 2.85 odd of a reduction in FBA. Kruskal Wallis test revealed a statistically significant relationship between Pirani severity score and Jain clinical outcome (p=0.01) as well as a statistically significant relationship between FBA and Jain clinical outcome (p=0.01). Conclusion The inital Pirani score inversely correlates with post treatment FBA. Poorer FBA and higher initial Pirani score is associated with a tendency to have a poorer Jain clinical outcome.